Ralstonia mannitolilytica sepsis: a case report - Owusu Michael; Acheampong Godfred; Owusu-Dabo Ellis; Annan Augustina; Osei Isaac...et al (BioMed Central, 2023)
This article is published by BioMed Central and is also available at https://doi.org/10.1186/s13256-019-2235-0